Study of Perceptions toward Humanitarian Forensic: a novel - Humanly Approach - Gupta , S; Parekh, U; Ratadiya , P (Journal of Indian Academy of Forensic Medicine, 2024)
Humanitarian Forensic Action, is a concept which has been brought by the International Committee of the Red Cross (ICRC), it refers to the applicability of forensic science and technology to address the needs of the victims of catastrophes for humanitarian, rather than criminal, purposes. Most of time Forensic Medicine and science is viewed in relation to crime, offence and justice involving victims or offenders. The concept of humanitarian forensic is predominantly focussed on dignified management of victims and grieved society. Forensic and forensic approaches are not much appreciated by community. There is a widely prevailing myth in the society that forensic is about investigation, crime, postmortem etc. People avoid taking help of forensic investigations unless it is absolutely essential. We started this project with the hypothesis that there are prevailing myths in community about forensic and lack of awareness about humanitarian forensics. We have collected 100 responses randomly in hospital settings. Out of which 62 respondents were male and 28 were female. Out of 100 respondents, 55 were from age group 20-30 years and with reasonably good education status. Validated 15 statements were asked for participant to respond on the Likert scale of 1-3 (agree, partially agree to disagree).